Cost awareness analysis on acute appendicitis treatment with BPJS Healthcare at Budi Kemuliaan Hospital, Batam - Anjari Wahyu Wardhani; Chriswardani Suryawati; Puji Harto (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Financial costs are recognized as one of the causes of lack access to adequate health services, not least in the treatment of Acute Appendicitis with BPJS Healthcare in Budi Kemuliaan Hospital, Batam. Data describing health workers' awareness of costs is still limited. Increasing awareness of health workers can encourage to increase treatment efficacy and reduce wasteful spending costs. Aims: This study objective was to analyze the cost awareness of health workers' in the efficiency of Acute Appendicitis treatment. Methods: This research was a qualitative descriptive study accompanied by direct observation on the implementation of clinical pathways and SOP in cases of Acute Appendicitis in Budi Kemuliaan Hospital, Batam. In this study also conducted interviews involving nine main informants and three triangulation informants. Result: There was a low awareness of costs identified in the implementation of clinical pathways and SOP in cases of Acute Appendicitis in general surgeons, resulting in high financing. There was also low management monitoring that could be seen in the incomplete TXT data. This had the potential to be a source of financial loss for hospitals. Conclusion: The lack of cost efficiency for Acute Appendicitis occurred due to lack of cost awareness and monitoring of hospital management. Efficiency could be seen in disposable materials components, but the incompleteness of TXT data could affect the calculation.